1996
DOI: 10.1161/01.cir.93.6.1230
|View full text |Cite
|
Sign up to set email alerts
|

Basis for Increased Microtubules in Pressure-Hypertrophied Cardiocytes

Abstract: Because we find persistent increases both in microtubules and in their biosynthetic precursors in pressure-hypertrophied myocardium, the mechanisms for this cytoskeletal abnormality must be sought through studies of the control both of microtubule stability and of tubulin synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 39 publications
5
62
0
2
Order By: Relevance
“…Microtubule (MT)-based processes were more pronounced in LCR than HCR. This can be related to our findings of elevated blood pressure (52) and pathological cardiac growth in LCR, since increased MT density and increased level of MT binding proteins are associated with pressure overload cardiac hypertrophy (9,40,45). MTs are also involved in hypoxic signaling, which was found to be different in HCR and LCR.…”
Section: Discussionsupporting
confidence: 66%
“…Microtubule (MT)-based processes were more pronounced in LCR than HCR. This can be related to our findings of elevated blood pressure (52) and pathological cardiac growth in LCR, since increased MT density and increased level of MT binding proteins are associated with pressure overload cardiac hypertrophy (9,40,45). MTs are also involved in hypoxic signaling, which was found to be different in HCR and LCR.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, previous studies have reported that hypertrophy-induced microtubule network expansion can sequester Smad3, preventing it from being accessed and phosphorylated by the transforming growth factor-β receptor. 37,38 This might explain although transforming growth factor-β expression was increased in Pak1-deficient hypertrophied hearts, yet it still failed to phosphorylate Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Because increases in both RV mass and RV cardiomyocyte microtubule network density stabilize by 2 wk after PAB placement (49), for the period of 2 wk through 4 wk after surgery there was either no further treatment in half of the PAB cats or treatment by pilling with the nonselective ␤-adrenergic blocker propranolol HCl extended release (40 mg po b.i.d.) in the other half of the PAB cats.…”
Section: Methodsmentioning
confidence: 99%